Codon bias of influenza a viruses and their hosts - Fancher, Keli C.; Hu, Wei (Scientific Research Publishing, 2011)
The Influenza A virus remains an annual and worldwide health concern due to its fast evolutionary rate. There are two major forms of Influenza evolution: drift, caused by mutations, and shift, which results from the exchange of genetic information between two gene segments. Using six synonymous codon usage bias indexes (GC content, ENC, SCUO, Codon Volatility, RSCU, and Odds Ratio), this study revealed the evolutionary drift patterns in the Influenza A viruses of avian, human, and swine origins as well as those of their hosts. We found that the variation of GC content across the 11 genes in Influenza A uniquely determines the viral origins in avian, human, and swine hosts. As was previously noticed in the Flaviviridae virus, a codon’s RSCU value of the Influenza viruses is positively correlated to the Odds Ratio of the dinucleotides contained within that codon. Additionally, the RSCU values of avian, human, and swine viruses and their corresponding hosts are similar, which is also true of Odds Ratio. Furthermore, the GC content, ENC, SCUO, and Codon Volatility are similar across the avian, human, and swine hosts; however, the RSCU and Odds Ratio of the hosts are distinct. Our findings expanded the knowledge on codon bias of Influenza viruses and their hosts.
Keywords: Influenza A; Evolutionary Drift; Codon Bias